Sosialisasi Pentingnya Gerakan Menabung Dengan Konteks Syariah Sejak Dini Pada Anak-Anak di Desa Jaranguda - Hairani Winarti; Putri Zahrani Purba; Titi Syahfitri Pane; Mutiah Khaira Sihotang Ma (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service program aims to socialize the importance of early saving habits to children using an Islamic financial approach, while also contributing to the village of Jaranguda in environmental preservation through the creation of organic and non-organic trash bins. The activities included preparation, socialization of the program, and participation in various social activities, such as group exercises, religious recitations, and the Independence Day celebration. Furthermore, the program developed the creativity of RA Nur Ilmi kindergarten students through games and skill-based activities. The results show that the program successfully fostered positive relationships between the students and the local community, raised awareness about the importance of saving and environmental management, and provided valuable experience for students in applying their knowledge within the community. The program is expected to continue with the support of various stakeholders to generate more long-term and significant impacts.